The Evolution of Russia’s Specialisation in Mutual Trade with the Countries of the EAEU - D. I. Ushkalova (Мир новой экономики, 2019)
The subject of our research was the analysis of changes in the specialisation of Russia in mutual trade with the countries of the Customs Union — the Common Economic Space — the Eurasian Economic Union since the beginning of the functioning of the single customs territory. The work aims to characterise the impact of the integration process within the CU-SES-EAEU on the commodity structure of Russian exports to the grouping countries and the possibilities for realising Russia’s export potential in the markets of the partner countries. The author examines the most important trends and factors in the evolution of the commodity structure of mutual trade within the EAEU and Russia’s exports to these countries, assesses the importance of the EAEU countries for the realisation of the export potential of Russia. The study concluded that the integration process had a positive effect on the commodity structure of Russia’s exports to the EAEU countries: during the unification, the share of mineral products in total exports decreased by one third, while the share of machinery and chemical products, food products and agricultural raw materials rose. The author substantiated that the EAEU states are the most important market for Russian goods with a high share of value added and their importance is increasing. Nevertheless, the prospect for further realisation of the export potential of Russia in the markets of the EAEU countries is very ambiguous and will be determined by two factors: the growth rate of the Russian economy and the real achievements in the field of shaping long-term integration effects.